IMMU-05. CCR2+ MYELOID-DERIVED SUPPRESSOR CELLS FROM MURINE GLIOMAS ARE SOURCED FROM THE BONE MARROW, SUPPRESS T CELL ACTIVATION, AND MIGRATE TO CCL2. (12th November 2021) - Takacs, Gregory; Kreiger, Christian; Luo, Defang; Flores-Toro, Joseph; Deleyrolle, Loic; Rahman, Maryam; Mitchell, Duane; Harrison, Jeffrey
Abstract: INTRODUCTION: Mounting evidence suggests infiltrating immune-suppressive cells contribute to immune checkpoint inhibitor resistance and poor survival in Glioblastoma (GBM) patients. We have previously shown glioma-associated monocytic-myeloid derived suppressor cells (M-MDSCs) express chemokine receptors CCR2 and CX3CR1. Genetic and pharmacologic targeting of CCR2 promoted sequestration of M-MDSCs in the bone marrow and, in combination with PD-1 blockade, slowed progression of KR158 and 005GSC murine gliomas. This combination treatment also enhanced infiltration of IFNg-producing T cells that were less exhausted. Although CCR2 + /CX3CR1 + cells display surface markers indicative of bone marrow-derived M-MDSCs, additional studies are needed to formally establish the source of these cells and to determine if they exhibit an immune-suppressive phenotype as well as migrate to the CCR2 ligands, CCL2 and/or CCL7. OBJECTIVE: Evaluate the source, migration, and immune suppressive function of CCR2 + /CX3CR1 + myeloid cells from glioma bearing mice. METHODS: To identify the source of CCR2 + /CX3CR1 + myeloid cells, chimeric wild type mice harboring bone marrow cells from transgenic CCR2 WT/RFP /CX3CR1 WT/GFP mice were generated. CCR2 + /CX3CR1 + cells were enriched from bone marrow obtained from either wild-type or CCR2 WT/RFP /CX3CR1 WT/GFP naïve and glioma-bearing mice in order to evaluate their immune suppressive phenotype and ability to migrate to CCL2 and CCL7. RESULTS: CCR2 + /CX3CR1 + cells are present in glioma isolates from chimeric mice, indicative of a bone marrow-derived cell population, and are detectable within the tumor microenvironment as early as 3 days post orthotopic implantation of KR158 cells; these cells accumulate as tumors increase in size (r=0.7605, p=0.007). CCR2 + /CX3CR1 + M-MDSCs isolated from the bone marrow of tumor bearing mice suppress CD8 + T cell production of IFNg and migrate to CCL2 more efficiently than CCL7. CONCLUSION: CCR2 + /CX3CR1 + cells from glioma bearing mice are derived from the bone marrow and represent an immune suppressive population that migrates to CCL2.